The political salience of language and religion: patterns of ethnic mobilization among Uyghurs in Xinjiang and Sikhs in Punjab - Reny, Marie-Eve (Ethnic and racial studies, 2009)
This article examines the reasons why the politicization of language has not been translated into disruptive forms of ethnic mobilization as opposed to the political salience of religions among the Uyghurs in Xinjiang throughout the 1990s and the Sikhs before and after the creation of Punjab in 1966. The article argues, from a structural-rationalist perspective, that language-based claims in Xinjiang and in Punjab have been accommodated by the respective central governments to a larger extent than religious claims have. Accommodation has taken the form of particular policies as well as greater incorporation of minority elites on the basis of language, which have in turn significantly reduced the possibilities of anti-regime sentiments and the incentives for disruptive forms of pressure on the basis of linguistic claims among the minority group. Religious claims have, however, not been accomodated in a similar way. (Ethnic and Racial Studies